Stories of change in nutrition: A tool pool - Gillespie, Stuart; van den Bold, Mara (International Food Policy Research Institute, 2015)
This paper—which draws on inputs to, and discussions at, a methods development workshop—highlights the various concepts, methods, and tools that SoC researchers are considering to measure nutrition-relevant change in their respective countries. The focus is on nutrition-relevant policy and practice. These tools apply to 11 subthemes, which are to some extent sequential within policy/programming cycles: (1) assessing the nutrition problem, (2) stakeholder and institutional analysis/mapping, (3) understanding enabling environments for nutrition, (4) agenda setting and political commitment for nutrition, (5) policy formulation and policy processes, (6) multisectoral coordination, (7) implementation and vertical coherence, (8) scaling up, (9) assessing capacity, (10) assessing finance, and (11) monitoring, evaluation, and accountability. Examining these various methods and tools together allows for a holistic consideration of the processes that—while challenging to document and measure—play a key role in improving nutrition-relevant policy and practice, which, in turn, drives national achievement in reducing malnutrition.